The efficiency increase of equipment work for the cleaning block of washing fluid - Surzhko, Tetiana; Savyk, Vasyl; Molchanov, Petro; Kaliuzhnyi, Anatoliy (Academic journal Industrial Machine Building Civil Engineering, 2020)
The efficiency increase of equipment work for the cleaning block of washing fluid by the vibrating sieve modernization has been observed. The approach to the most acceptable values of constructive parameters of vibrating sieve using analytical methods and the usage of the rheological mixture model that allows determining the dynamic and technological characteristics of the vibrating machine and environmental impact on the form board and bottom has been implemented. The influence of the working body (grid) of the vibrating sieve on the rough cleaning of drilling mud from sludge has been investigated. A method for reducing complex hybrid systems to systems with a finite number of freedom degrees has been proposed, and the reduced parameters had the ability to adequately describe the wave processes of a continuous medium.